P 40 : Plakate aus der DDR. (Berlin : Verband der Grafik-Designer der DDR, 1990)
Von Appen, Karl ; Arnold, Ingo ; Baarmann, Kerstin ; Bärmisch, Meinhard ; Bahra, Bob ; Baltzer, Hans ; Bauer, Peter ; Baus, Georg ; Beck, Karl-Heinz ; Bertram, Axel ; Blendinger, Günter ; Blumenthal, Regine ; von Bodecker, Albrecht ; Böhm, Walter ; Boehland, Johannes ; Bofinger, Manfred ; Brade, Helmut ; Büttner, Helmut Feliks ; etc.
boek